2006
DOI: 10.1029/2005je002599
|View full text |Cite
|
Sign up to set email alerts
|

North‐south roughness anisotropy on Venus from the Magellan Radar Altimeter: Correlation with geology

Abstract: [1] Analysis of the Doppler spectrum of Magellan Radar Altimeter echoes has revealed the spatially coherent deflection of the echo center from the nadir point (Tyler et al., 1992). We present and analyze a global map of the Doppler centroid of the radar altimeter echo, which, for the plains of Venus, characterizes the degree of anisotropy of the surface roughness in the north-south direction at scales from decimeters to kilometers. We found a global hemispherical trend of roughness anisotropy: on average, equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The observed bands of increased asymmetry at the periphery of the crater‐related deposit indicate wind reworking of the deposit material in the areas where deposits are thin. This asymmetry coincides with microdune shapes formed by equatorward surface winds prevalent in the northern hemisphere of Venus [ Bondarenko et al , 2006]. The map of the rms slopes for the crater Boleyn area is shown in Figure 8c.…”
Section: Ddf Scattering Anisotropy As a Signature Of Wind Erosionsupporting
confidence: 59%
See 3 more Smart Citations
“…The observed bands of increased asymmetry at the periphery of the crater‐related deposit indicate wind reworking of the deposit material in the areas where deposits are thin. This asymmetry coincides with microdune shapes formed by equatorward surface winds prevalent in the northern hemisphere of Venus [ Bondarenko et al , 2006]. The map of the rms slopes for the crater Boleyn area is shown in Figure 8c.…”
Section: Ddf Scattering Anisotropy As a Signature Of Wind Erosionsupporting
confidence: 59%
“…Three areas of very strong E‐W asymmetry (the observed difference is up to 8 dB), and interpreted as microdune fields [ Weitz et al , 1994], are localized in the western parts of parabolas near craters Stowe, Eudocia and Guan Daosheng. Widespread weaker scattering anisotropy over the plains of Venus has been reported by Kreslavsky and Vdovichenko [1999] and Bondarenko et al [2006]. These have been interpreted to represent the widespread occurrence of eolian features, perhaps, microdunes.…”
Section: Ddf Scattering Anisotropy As a Signature Of Wind Erosionmentioning
confidence: 70%
See 2 more Smart Citations
“…The apparent lack of dunes could, however, be partially an observational effect. Analysis of radiophysical properties in several regions of Venus by Bondarenko et al [2006] revealed a noticeable east-west asymmetry in the radar returns which was interpreted as possible dunes/ripples of meter to decameter size range.…”
Section: Current View Of Surface Features and Unitsmentioning
confidence: 99%